Variáveis associadas à qualidade de vida e à autoestima em pessoas com vitiligo - Galliez, Camila Franciss (2021)
Vitiligo is a dermatosis that causes the appearance of depigmented areas on the skin. This study aimed to investigate the quality of life and self-esteem of vitiligo patients, as well as to identify triggering factors, possible psychological repercussions and different ways of dealing with the symptom. The participants were 312 individuals over 18 years old and members of the Facebook group "Vitiligo Brasil" who completed an online questionnaire that included: 1) Characterization form; 2) Rosenberg's Self-Esteem Scale; 3) Specific Questionnaire on Quality of Life in Vitiligo (VitiQoL-PB); 4) Questionnaire about experiences with vitiligo; 5) Questionnaire with the location of vitiligo. The data were analyzed quantitatively and qualitatively, in the light of psychosomatics and analytical psychology. Statistical analysis of the results revealed significant correlations between income, education, age and age of onset of vitiligo. It was observed that the lower the level of education and income, the greater the impact of vitiligo on self-esteem and quality of life. It was also found that there was a greater impact on the quality of life of those who were not in a relationship. The participants' reports demonstrate that vitiligo tends to impact self-image, social life, relationships and mental health, as well as coping resources. The existence of a virtual space for acceptance and sharing of experiences, as in the case of the group studied, also appears to be a protective measure in relation to the psychological suffering caused by vitiligo